STUDY AT HOME: ANALISIS KESULITAN BELAJAR MATEMATIKA PADA PROSES PEMBELAJARAN DARING - Yuliza Putri Utami; Derius Alan Dheri Cahyono (Universitas Teknokrat Indonesia, 2020)
AbstractThe e-learning study at home education system is in accordance with the 2013 curriculum. However, when the e-learning application is too difficult, it is likely that students are not able to learn mathematics optimally, as well as the amount of data that must be delivered but the internet or network access becomes slow, of course it is will disrupt student activities. This study aims to determine the learning difficulties of students towards mathematics e-learning at home. The research method used is descriptive research method. The study involved high school / MA students with data collection techniques and information through a student questionnaire response instrument using Google forms and the research subjects numbered 30 students. The student response contained 31 statement items which were the descriptions of the indicators. Indicator to measure students 'responses regarding students' learning difficulties to mathematics through the e-learning system at home. Based on the average student achievement regarding learning difficulties in mathematics e-learning that is 75% by having the lowest achievement value by students namely the implementation of interactions, assignments and teaching materials in online learning by 73% and the highest indicator achieved by students namely technical signal constraints and the inability to learn online (e-learning) that is equal to 77% and for testing the validity shows that all items are valid statements, this is because ???????????????????????? ???????????????????????? and Cronbach Alpha value 0.839 reliability coefficient 0.6. After calculated using SPSS 23.Keywords: Difficulty learning mathematics, E-learning, studying at home